2011
DOI: 10.1007/7854_2011_197
|View full text |Cite
|
Sign up to set email alerts
|

MR Spectroscopic Studies of the Brain in Psychiatric Disorders

Abstract: The measurement of brain metabolites with magnetic resonance spectroscopy (MRS) provides a unique perspective on the brain bases of neuropsychiatric disorders. As a context for interpreting MRS studies of neuropsychiatric disorders, we review the characteristic MRS signals, the metabolic dynamics,and the neurobiological significance of the major brain metabolites that can be measured using clinical MRS systems. These metabolites include N-acetylaspartate(NAA), creatine, choline-containing compounds, myo-inosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(206 citation statements)
references
References 243 publications
(327 reference statements)
6
196
0
Order By: Relevance
“…Under basal conditions, the MRS GABA signal arises mostly or almost entirely from the large cytoplasmic GABA pool in GABAergic neurons, the functional significance of which is not known (22). Therefore, MRS GABA seems unlikely to reflect primarily the activity of GABAergic interneurons, including those within gamma-generating networks (10).…”
Section: Discussionmentioning
confidence: 99%
“…Under basal conditions, the MRS GABA signal arises mostly or almost entirely from the large cytoplasmic GABA pool in GABAergic neurons, the functional significance of which is not known (22). Therefore, MRS GABA seems unlikely to reflect primarily the activity of GABAergic interneurons, including those within gamma-generating networks (10).…”
Section: Discussionmentioning
confidence: 99%
“…Here, to our knowledge, we characterized for the first time, through HR-MAS NMR analysis, the metabolic fingerprint of intact human neuronal SH-SY5Y cells and their culture medium. Metabolites with an important role in the central nervous system functionality have been identified (Maddock and Buonocore 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because phosphatidylcholine, as a primary phospholipid, is found at higher levels in myelin, cell membranes and brain parenchyma [45] , it may have a crucial role for development of neuropsychiatric disorders in dogs as in humans [45] . In addition, excessive serum levels of NEFA, as observed in the present study, were reported to enhance oxidative stress [46] leading to several neuropsychiatric diseases including OCD [47] .…”
Section: Discussionmentioning
confidence: 99%